Biographie und Bildungskultur Personendarstellungen bei Plinius dem Jüngeren, Gellius und Sueton - Pausch, Dennis (Millennium-Studien / Millennium Studies, 2012)
What role did biographies play for the intelligentsia of the 2nd century AD and what literary forms were used by contemporary authors in their personal portrayals? These two questions have led to this cross-genre investigation of the personal portraits in the letters of Pliny the Younger, in the miscellaneous work of Gellius, and in the Lives of the Caesars by Suetonius.